2018
DOI: 10.14710/jitaa.43.2.94-106
|View full text |Cite
|
Sign up to set email alerts
|

Non-genetic factor and genetic parameter analysis for growth traits in Sumba Ongole (SO) cattle

Abstract: The aim of this study was to evaluate non-genetic factors and genetic parameters of the growth traits in Sumba Ongole (SO) cattle. The growth traits were consisted of birth weight (BW), weaning weight (WW), yearling weight (YW), average daily gain of pre-weaning (ADG1) and post-weaning (ADG2). Data from 143 heads of SO cattle (year 2011 to 2016) which raised at PT KAR were used in this study. Generalized Linear Model (GLM) analysis was performed to evaluate non-genetic effect including sex, year of birth, gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The h 2 value of BW in Bali cattle at WNT province was included of high category (h 2 >0.30) with low of SE value. High category of h 2 value for BW was showed in Red Chittagong (0.50), Horro (0.62), Nellore (0.37), Bali (0.85), Brahman (Afroz et al, 2011;Abera et al, 2013;Regatieri et al, 2012;Kaswati et al, 2013;Rakwadi et al, 2014;Rahman et al, 2015;Putra et al, 2018). Moderate of h 2 value (0.10 < h 2 < 0.30) for BW was showed in Vrindavani (0.29), Tuli (0.21), Charolais (0.23) and Ongole cross (0.28) cattle (Singh et al, 2010;Rakwadi et al, 2014;Vostry et al, 2015;Hartati et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The h 2 value of BW in Bali cattle at WNT province was included of high category (h 2 >0.30) with low of SE value. High category of h 2 value for BW was showed in Red Chittagong (0.50), Horro (0.62), Nellore (0.37), Bali (0.85), Brahman (Afroz et al, 2011;Abera et al, 2013;Regatieri et al, 2012;Kaswati et al, 2013;Rakwadi et al, 2014;Rahman et al, 2015;Putra et al, 2018). Moderate of h 2 value (0.10 < h 2 < 0.30) for BW was showed in Vrindavani (0.29), Tuli (0.21), Charolais (0.23) and Ongole cross (0.28) cattle (Singh et al, 2010;Rakwadi et al, 2014;Vostry et al, 2015;Hartati et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Factor of sex, year, parity and season also affect to BW in other Indonesian Ongole cross cattle (Hartati et al, 2015). Meanwhile, Putra et al (2018) reported that two factors of year and season were affected of BW in Sumba Ongole cattle. According to the previous studies, the BW of Bali calves in Bali island was highest than in two islands at WNT province.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Body measurements of heart girth had high correlation value with body weight (Kashoma et al, 2011;Serkan & Bozkurt, 2009;Alsiddiq et al, 2010). In cattle, the high heritability (h 2 ) value were reported in heart girth (Khan et al, 2016) and body weight (Putra et al, 2014;Gunawan & Jakaria, 2011;Kaswati et al, 2013;Hartati et al, 2015;Putra et al, 2018). High h 2 value in both traits reveals that these traits can be increased through selection program.…”
Section: Introductionmentioning
confidence: 99%
“…
Holstein (FH) male calves could be used as a potential meat source due to the higher average daily gain (ADG) compared to Indonesian local cattle like Ongole crossbreed (0.86 to 0.92 kg head -1 day -1 vs 0.33 to 0.64 kg head -1 day -1 ; (Putra et al, 2018). But in Abstract | Urea addition into feed to some extent has been shown to increase crude protein content and improve feed efficiency.
…”
mentioning
confidence: 99%